Effects of stabilizing materials on soil Cd bioavailability, uptake, transport, and rice growth - Meizhen Xu; Fei Luo; Feng Tu; Gul Rukh; Zhengqian Ye; Zhongqiang Ruan; Dan Liu (Frontiers in Environmental Science, 2022)
Cadmium, a widespread toxic heavy metal in farmland soils, is harmful to human health. A field experiment was conducted to investigate the effects of biochar and biochar-based fertilizers on soil pH, organic matter, and available Cd, as well as rice Cd uptake and translocation. The results showed that rice biomass was significantly increased after both the application of biochar and high rate of biochar-based fertilizers at the tillering stage. The biomass and plant height of rice were improved at filling and maturity stages. Soil pH was significantly increased with the application of biochar but not with the biochar-based fertilizer. The amendments of biochar and biochar-based fertilizers had no significant (p < 0.05) influence on soil organic matter content. The concentration of available Cd in soil and the concentration of Cd in rice were decreased with the application of different amounts of biochar and biochar-based fertilizers in the mature stage. However, this effect was much greater under biochar amendment. Compared to the control, the concentration of available Cd in soil was reduced by 33.09% with the low application rate of biochar, while that was reduced by 18.06% with the high application rate of biochar. The lowest bioaccumulation factor was due to the high concentration of biochar and biochar-based fertilizers. It is concluded that biochar and biochar-based fertilizers particularly at a high addition rate are appropriate for decreasing Cd mobility and improve soil quality for contaminated paddy soils. The study showed a method for the safe production of rice in Cd-polluted farmlands by using a high application rate of biochar or carbon-based fertilizers.